ANALISIS KANDUNGAN MINYAK ATSIRI EKSTRAK RIMPANG KENCUR (Kaemprefia galangan l.,) DENGAN MENGGUNAKAN METODE KLT - Fikayuniar, Lia; Hanita, Icha; Aulia, M Azriel; Syarifah, Nadia Siti; Khairani, Risda Aulia; Pijriah, Sulis Salsa; Agrestia, Tasya (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Simplicia is a natural ingredient that is dried and used as medicine and has not undergone any processing involving any chemical processes. Simplicia is divided into three types, namely animal, pelican and vegetable simplicia. Drying simplicia must be done under appropriate conditions to avoid loss of active substance content. This research uses galangal (Kaempferia galanga) as the simplicia used. Galangal is used in various traditional treatments, such as rheumatism, asthma, stomach ulcers, malnutrition, diarrhea, coughs, fever, as a concoction to increase stamina and digestive tract disorders. The chemical ingredients in kencur simplicia, such as essential oils and curcuminoids, have good properties for the body. This research uses a thin layer chromatography method to identify the essential oil content in galangal rhizomes.